A rare case of acute myeloid leukemia with t(12;19)(q13;q13). (2020) - Chebly, Alain; Haddad, Fady Gh; Bassil, Josiane; Yammine, Tony; Korban, Rima; Semaan, Warde; El Karak, Fady; Kourie, Hampig Raphael; Farra, Chantal
Abstract: Acute myeloid leukemia (AML) is characterized by chromosomal abnormalities affecting both prognosis and course of treatment. While most AML patients have well described chromosomal aberrations, around 10% present with rare chromosomal abnormalities. We herein, report a rare balanced translocation t(12;19)(q13;q13) in a 66-year old M5-AML patient identified by Conventional cytogenetic analysis and confirmed by SNP array. We suggest that t(12;19) as a sole chromosomal abnormality could be associated with a poor prognosis. Further studies are needed to understand the molecular basis of this translocation in AML.